Association of Herd Size with Stillbirth and Dystocia Rates in Japanese Black Cattle - Moe Misaka; Mizuho Uematsu; Go Kitahara; Takeshi Osawa; Yosuke Sasaki (Animals, 2022)
The objective of this study was to investigate the effect of herd size on stillbirth and dystocia rates; the relationships between herd size, calving season, parity, and gestation length in Japanese Black cattle were also explored. Data were collected for 41,184 calvings from 15,512 animals on 905 farms between 2006 and 2010. In this study, herds were classified into three groups based on size: small (1–10 cows), medium (11–50 cows), and large (≥51 cows). Herd size had an effect on the dystocia rate (p < 0.05) but not the stillbirth rate. Additionally, interactions between herd size and gestation length were associated with the dystocia rate (p < 0.05), and the dystocia rate was the highest in small herds, followed by medium and large herds for cows with a gestation length of 281–300 days, which is considered a pregnancy of normal duration. In summary, in Japanese Black cattle, there were different effects of herd size on the stillbirth rate and dystocia rates, as herd size was associated with the dystocia rate but not with the stillbirth rate.